2009
DOI: 10.1200/jco.2008.18.4028
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel With Cyclophosphamide Is Associated With an Overall Survival Benefit Compared With Doxorubicin and Cyclophosphamide: 7-Year Follow-Up of US Oncology Research Trial 9735

Abstract: With longer follow-up, four cycles of TC was superior to standard AC (DFS and OS) and was a tolerable regimen in both older and younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
308
3
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(342 citation statements)
references
References 23 publications
12
308
3
11
Order By: Relevance
“…Later, anthracycline combinations were found to be slightly but significantly more effective than the CMF regimen [2]. More recently, several adjuvant phase III trials have shown that taxane regimens further reduce the likelihood of recurrence and death, compared to anthracycline-containing combinations [3][4][5][6][7][8][9][10], but the absolute benefit was again small, and some trials were unable to show any advantage for the taxane arm [11,12]. Taxanes and anthracyclines can induce some acute and chronic toxicities of considerable clinical concern.…”
Section: Introductionmentioning
confidence: 99%
“…Later, anthracycline combinations were found to be slightly but significantly more effective than the CMF regimen [2]. More recently, several adjuvant phase III trials have shown that taxane regimens further reduce the likelihood of recurrence and death, compared to anthracycline-containing combinations [3][4][5][6][7][8][9][10], but the absolute benefit was again small, and some trials were unable to show any advantage for the taxane arm [11,12]. Taxanes and anthracyclines can induce some acute and chronic toxicities of considerable clinical concern.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, taxanes may be given as an alternative to anthracyclines to alleviate cardiac risks. Use of docetaxel and cyclophosphamide (TC) has provided a significant survival benefit over AC after 7 years median follow-up, irrespective of age [52]. Although febrile neutropenia may be an issue, this can be minimized with granulocyte colony stimulating factors (G-CSF) primary prophylactic administration [53,54].…”
Section: Triple Negative Ebcmentioning
confidence: 99%
“…An anthracycline-free taxane doublet (docetaxel/cyclophosphamide) demonstrated superior disease-free and overall survival compared with doxorubicin/cyclophosphamide in the treatment of early stage breast cancer with an acceptable safety profile, with grade 3/4 neutropoenia of 61% and no cardiotoxicity [48]. As a consequence, a multicenter Phase II (8) pilot trial of weekly nab-P/cyclophosphamide was conducted to test the safety and tolerability of this combination in early-stage breast cancer.…”
Section: Adjuvant Studiesmentioning
confidence: 99%